KEWENANGAN PEMERINTAH KOTA BEKASI DALAM MENURUNKAN ANGKA KEMISKINAN DI KOTA BEKASI TAHUN 2022-2023: The authority of Bekasi city government in reducing poverty rates in Bekasi city 2022-2023 - Adilah Maharani; Eko Primananda (Faculty of Law, Universitas Trisakti, 2025)
Health and food safety are among the concurrent affairs that fall under the responsibility of both the central This research examines the authority of the Bekasi City Government in reducing poverty rates for the 2022- 2023 period based on Local Regulation Number 4 of 2018 on Poverty Alleviation. The identification in Bekasi City is a serious challenge, with the number of poor residents reaching 137,390 people in 2022. The study employs a normative juridical method with a socio-legal approach, utilizing primary and secondary data from legal materials. The result and conclusion indicate that the Bekasi City Government has implemented various poverty alleviation programs such as food assistance, cash assistance, Family Hope Program (PKH), and community economic empowerment with a total budget of IDR 116.4 billion. These programs successfully reduced the poverty percentage from 4.43% to 4.10%. The government also developed the SI IJAH system with 19 assessment variables for accurate data collection and implemented extreme poverty management programs through the Regional Poverty Alleviation Coordination Team (TKPKD). The success of these programs was supported by data integration from the Integrated Social Welfare Data (DTKS), Central Bureau of Statistics (BPS), and the Acceleration of Extreme Poverty Elimination by the Coordinating Ministry of Human Development and Culture (P3KE Kemenko PMK) to ensure program targeting accuracy.